Vox lux [videorecording (DVD)] - Corbet, Brady, 1988-; Portman, Natalie, 1981-; Law, Jude, 1972-; Martin, Stacy, 1991- (Universal Pictures Home Entertainment, 2019)
The story of Celeste's rise from the ashes of a national tragedy to stardom. It follows her life from 1999 to 2017 including her survival of a violent tragedy as a teenager, her rise to fame with the help of her sister and talent manager, and her mounting a comeback after a scandal.